2020
DOI: 10.1590/1980-265x-tce-2018-0348
|View full text |Cite
|
Sign up to set email alerts
|

Factors Associated With the Clinical Deterioration Recognized by an Early Warning Pediatric Score

Abstract: Objective: To identify the factors associated with clinical deterioration recognized by a Pediatric Early Warning Score. Method: A cross-sectional study conducted in a tertiary pediatric public hospital with 271 children aged from zero to ten, hospitalized between May and October 2015. For the identification of the children with and without signs of clinical deterioration, the translated, adapted and validated version of the Brighton Pediatric Early Warning Score was applied to the Brazilian context. Logistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 24 publications
0
1
0
3
Order By: Relevance
“…17 Miranda et al found that an elevated PEWS was associated with clinical signs of deterioration with an AUC of 0.92, sensitivity of 74%, and specificity of 96%. 19 Chaiyakulsil and Pandee in their study in the emergency department of a university hospital found elevated PEWS was associated with admission to the hospital with an AUC of 0.73, sensitivity of 78%, and specificity of 60%, and higher scores were associated with ICU admission, with an AUC of 0.98, sensitivity of 100%, and specificity of 91%. 20 In their review of the PEWS in resource-limited settings, Brown et al suggested that the PEWS may aid in the triage of large numbers of hospitalized patients and help staff identify those who require immediate attention without the need for extensive pediatric experience.…”
Section: Discussionmentioning
confidence: 92%
“…17 Miranda et al found that an elevated PEWS was associated with clinical signs of deterioration with an AUC of 0.92, sensitivity of 74%, and specificity of 96%. 19 Chaiyakulsil and Pandee in their study in the emergency department of a university hospital found elevated PEWS was associated with admission to the hospital with an AUC of 0.73, sensitivity of 78%, and specificity of 60%, and higher scores were associated with ICU admission, with an AUC of 0.98, sensitivity of 100%, and specificity of 91%. 20 In their review of the PEWS in resource-limited settings, Brown et al suggested that the PEWS may aid in the triage of large numbers of hospitalized patients and help staff identify those who require immediate attention without the need for extensive pediatric experience.…”
Section: Discussionmentioning
confidence: 92%
“…A importância da escala é alertar a equipe e nortear condutas clínicas frente à somatória dos resultados obtidos, possibilitando desfechos mais favoráveis. Estudos mostram a utilização da escala por times de resposta rápida constituída por profissionais da área da saúde, consolidados à rotina assistencial dos grandes hospitais, possibilitando respostas mais positivas e contribuindo para o processo de segurança do paciente (Miranda et al, 2020).…”
Section: Introductionunclassified
“…Para atender pacientes pediátricos nesse cenário, foi desenvolvida uma ferramenta utilizando os mesmos princípios de avaliação de alterações fisiológicas adaptadas à realidade pediátrica, os chamados Pediatric Early Warning Score (PEWS), desenvolvidos e validados a fim de identificar precocemente sinais de alerta em crianças hospitalizadas (Miranda et al, 2020).…”
Section: Introductionunclassified
See 1 more Smart Citation